Abstracts of the Combined Conference of the Parapsychological Association and the Society for Scientific Exploration. (Journal of Parapsychology)
The article offers information on the abstracts presented at the Combined Conference of the Parapsychological Association and the Society for Scientific Exploration (SSE-PA Breakthrough, 2022). Topics include research on consciousness, subtle energies, remote viewing, and the psychology of skeptics in the field of parapsychology. The conference aims to explore new knowledge and breakthroughs in the study of psi phenomena and its applications in various fields.